Assessing Residents' Perception of Their Ability to Manage Chronic Musculoskeletal Pain in HIV-Infected Patients. (4th October 2017) - Twardy, Brandon; Monday, Lea; Maroof, Shahram; Chakur, Nichole; Weinberger, Jarrett; Veltman, Jennifer
Abstract: Background: Chronic pain in HIV infected patients is common in the ambulatory setting, the majority of which is musculoskeletal (MSK). Addressing patient's pain is essential but physicians often fail to adequately manage MSK pain. Additionally, HIV patients with chronic non-cancer pain (CNCP) have a 2-fold increase in the risk of opioid misuse compared with the general population. We sought to determine the extent of pain complaints and opioid prescriptions in our HIV clinic as well as assess the comfort and ability of our residents to develop a comprehensive pain management plan. Methods: We performed a chart review of all patients seen by our Internal Medicine (IM) residents in the HIV primary care in Detroit, MI from 01/2017-05/2017 and collected demographic and pain-related data. We also surveyed IM residents assigned to HIV primary care clinic on their knowledge and comfort developing management plans for CNCP. IRB waiver was obtained. Results: A total of 249 HIV infected patients were seen from January 2017 to May 2017. Forty-one of 249 (16%) of patients were identified as a having CNCP and of these patients, all were treated with opioids. MSK symptoms encompassed 28/41 (68%) of the total complaints. This included back pain ( n = 20), lower extremity pain ( n = 10), and upper extremity pain ( n = 2). Only 5/41 (17%) patients were prescribed physical therapy for their pain complaints. Fifteen of 20 (75%) of IM residents responded to a survey on their comfort and knowledge in treating CNCP. None of the 15 (0%) felt completely comfortable developing a plan for CNCP, 2/15 (13%) felt their examination skills were adequate in assessing MSK symptoms in patients with CNCp. 12/15 (80%) felt working in collaboration with a physical therapist (PT) would be beneficial in developing effective treatment plans and 10/15 (67%) thought working in collaboration with a PT would help further develop their examination skills. Conclusion: A survey of our IM residents has found gaps in both knowledge and comfort in CNCP pain management and high levels of opioid prescriptions in our HIV primary care clinic. Here we provide evidence that IM residents require additional training in treating CNCP in HIV patients and are interested in multidisciplinary approaches to development of non-pharmacologic treatment plans for HIV infected patients with CNCP. Disclosures: All authors: No reported disclosures.